Willingness to perform induced abortion and associated factors among graduating midwifery, medical, nursing, and public health officer students of University of Gondar, Northwest Ethiopia: institution based cross sectional study - Mihretu Molla Enyew (BMC, 2020)
Abstract Background In developing countries, abortion is often unsafe and a significant cause of maternal morbidity and mortality accounting for about 8% (4.7-13.2%) of maternal mortality worldwide. Internationally, safe abortion services are recognized as reducing maternal mortality, and liberalized abortion laws are associated with reduced mortality resulting from unsafe abortion procedures. However, health care providers have moral, social and gender-based reservations that affects their willingness towards providing induced abortion services. The purpose of this study was to assess willingness to perform induced abortion and associated factors among graduating Midwifery, Medical, Nursing, and Public health officer students of University of Gondar. Methods Institution based cross sectional study was conducted from March 29 to May 30, 2019. All graduating students available during data collection period were considered as study population. Stratified simple random sampling technique was used to select 424 study participants. Pre tested, semi- structured, self-administered questionnaire was used to collect data. Data analysis was done using SPSS version 20. Ethical clearance was obtained from School of midwifery under the delegation of institutional review board of university of Gondar. Results Two hundred ninety students out of 424 students were willing to perform induced abortion for indications supported by Ethiopian abortion law, making a proportion of 68.4% (95%Cl: 64.2, 72.9). Sex (Being male (AOR = 4.89, 95%CI: 3.02, 7.89)), religion (being orthodox than protestant (AOR = 10.41, 95%CI: 3.02, 21.57)), being Muslim than protestant (AOR = 5.73, 95%CI: 1.37, 15.92)) and having once or less a week religious attendance (AOR = 2.00, 95% CI: 1.20, 3.34) were factors associated with willingness towards performing induced abortion. Conclusions According to this study willingness of students towards providing induced abortion services was good. However female students, protestant followers and those students with more than once a week religious attendance should be encouraged to support women's access to induced abortion services by referring them to other health care professionals willing to provide induced abortion services.